A Case of Orbital Rosai-Dorfman Disease with IgG4 Positive Plasma Cells. (22nd July 2013) - Mudhar, Hardeep Singh; Duke, Roseline
Abstract: A case of a 9-year-old Black African male with right-sided proptosis is presented. The clinical interpretation was that of orbital rhabdomyosarcoma and an incisional biopsy was performed. This revealed the typical features of Rosai-Dorfman disease, featuring S100 positive non-Langerhans histiocytes with emperipolesis. There were also numerous plasma cells in the biopsy, in the more fibrotic areas. More than 40% of these plasma cells were positive for IgG4. This case represents the first case in the orbit to make the association of IgG4 plasma cell positivity with Rosai-Dorfman disease. Potential associations are discussed, and the relevance of this finding to ophthalmic pathology interpretation and differential diagnosis are highighted.